Ühe ülendamisaklamatsiooni vorm ja sisu apostel Pauluse koolkonna kõrgkristoloogias: perikoobi Ef 1:20–23 eksegeetiline ja religioonilooline analüüs - Naab, Ergo (Usuteaduslik Ajakiri, 2016)
The Form and Content of One Elevation-Acclamation in DeuteroPauline High Christology: the Exegetical and Religio-Historical Analysis of the Pericope Eph 1:20-23. Bible passage Eph 1:20-23 consists ofvery influential Christological statement proclaimed in early Christianity. This article discusses the elevation motive of Christ, which is one of the most prominent constructions in the New Testament writings. It is part of the kerygma (proclamation) and on this notion are based all other schemes and dogmas of Christian thought. The elevation motive is actually included in the royal psalm 110:1, the most cited inauguration-oracle in the Old Testament („Sit at my right hand until I make your enemies your footstool”). The main topic of the paper focuses on four ancient Greek words that are related with principalities, powers, and the content of the above-mentioned statement. The author of the Deutero-Pauline epistle used Hellenistic epistolography with citations from Hebrew scripture and fashioned the form of the statement according to his own liturgical purposes. There is no scholarly consensus related to the meaning of the four words of principalities and powers, but quite clear allusions indicate to the visible Roman power which an average first century person had to live with.